(untitled) (Prostor, 2022)
In a period of transition, sudden and numerous economic, social and political changes led to an uncontrolled growth of cities in Kosovo. The rapid population growth and geographical expansion of cities challenged planned development, which resulted in an uncontrolled urban expansion. This paper includes a historical review of housing policies in Kosovo from 1947 until 2021. The research starts with the period after World War II, which marked the beginning of a trend of rapid construction all over Europe, both due to urban growth and as a result of the destruction of many residential buildings. It analyses the implementation of policies, laws, housing regulations in residential neighbourhoods and, in particular, multi-unit housing in Kosovo. The research also includes housing policies in some of the most developed countries in Europe, to give the reader a clearer understanding and comparison of European and Kosovar housing issues.